2006
DOI: 10.1017/s0022215106000454
|View full text |Cite
|
Sign up to set email alerts
|

Ear, nose and voice problems in children with orofacial clefts

Abstract: The purpose of this study was to compare the prevalence of ear, nose and particularly voice problems in groups of children with cleft palate (CP) and with unilateral cleft lip, alveolus and palate (UCLP). On the basis of history, regular otorhinolaryngological examinations and hearing tests, the prevalence of different pathologies was assessed in 80 CP children (35 boys and 45 girls) and 73 UCLP children (47 boys and 26 girls). Ear pathology was reported in 53.8 per cent of CP children and in 58.9 per cent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 16 publications
2
42
1
2
Order By: Relevance
“…Therefore the sex distribution is likely due to the predomi- 123 nance of this type of cleft in the studied sample. This sex distribution does not correlate with that reported by other studies, which have reported a female preponderance [4][5][6]. The reason for this is likely to be a difference in the sample studied.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Therefore the sex distribution is likely due to the predomi- 123 nance of this type of cleft in the studied sample. This sex distribution does not correlate with that reported by other studies, which have reported a female preponderance [4][5][6]. The reason for this is likely to be a difference in the sample studied.…”
Section: Discussioncontrasting
confidence: 95%
“…We had noticed clinically a high number of children with non-syndromic cleft palate having external ear abnormalities. Existing studies do not document the status of the external ear in children with cleft palate [4][5][6] even though there have been case reports suggesting presence of external ear deformities in individuals with cleft palate [7]. Therefore, to obtain the relevant data and to systematically document the clinically signifi cant otopathology in the child with cleft palate, a cross sectional study was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…32,28 Studies relating sustained auditory attentiveness and cleft lip and palate were not found in our review; we thus tried to correlate this study with those that included subjects with a history of recurring otitis. [9][10][11][12][13] We were aware that these studies were subject to methodological issues, including the retrospective studies that contain biases and imprecise methods for detecting OME. 39,41 Since OME may be silent in over 50% of cases, it is hard to study; finding it requires careful medical surveillance independently from symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We stress the presence of positive history of otitis media as a factor of probable influence on the performance of children in the AFT-R test, because of middle ear alterations in the population with labio-palatine fissure be almost a consensus 35,36 thus inferring that it must have been present at some point during their lives, which can impact test results. Literature 35,36 shows that children with labio-palatine fissures have longer periods of sensorial privation, caused by middle ear infection when compared to those without this craniofacial malformation.…”
Section: Discussionmentioning
confidence: 99%
“…Literature 35,36 shows that children with labio-palatine fissures have longer periods of sensorial privation, caused by middle ear infection when compared to those without this craniofacial malformation.…”
Section: Discussionmentioning
confidence: 99%